2011
DOI: 10.1021/es2000694
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Contribution of Free Hydroxyl Radical in Organic Matter-Sensitized Photohydroxylation Reactions

Abstract: Photochemical formation of reactive oxygen species from dissolved organic matter (DOM) is incompletely understood, especially in the case of hydroxyl radical (•OH) production. Many studies have used various probes to detect photochemically produced •OH from DOM, but the fundamental reactions of these probes are not necessarily specific for free •OH and may also detect lower-energy hydroxylation agents. In this study, two tests were applied that have previously been used as a diagnostic for the presence of free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
220
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(230 citation statements)
references
References 40 publications
10
220
0
Order By: Relevance
“…20 The most likely explanation for the contrasting literature findings about CDOM/humic acids and CBZ phototransformation, is that CDOM produces • OH along with triplet states. 13,48,49 CDOM samples that produce more • OH could account for CBZ photodegradation enhancement, those producing less would account for the opposite effect. Field data of CBZ persistence that allow comparison with the model have been reported for Lake Greifensee, Switzerland.…”
Section: Resultsmentioning
confidence: 99%
“…20 The most likely explanation for the contrasting literature findings about CDOM/humic acids and CBZ phototransformation, is that CDOM produces • OH along with triplet states. 13,48,49 CDOM samples that produce more • OH could account for CBZ photodegradation enhancement, those producing less would account for the opposite effect. Field data of CBZ persistence that allow comparison with the model have been reported for Lake Greifensee, Switzerland.…”
Section: Resultsmentioning
confidence: 99%
“…However, concentrations involved are much higher than those found in environmental waters. Organic compounds that occur in aqueous environments can be transformed by a variety of abiotic and biological pathways, among which direct photochemistry and photogenerated reactive species such as hydroxyl radical ( • OH), carbonate radical (CO 3 •− ), singlet oxygen ( 1 O 2 ) and triplet states of Chromophoric Dissolved Organic Matter ( 3 CDOM*) (Mack and Bolton, 1999;Canonica et al, 1995 andCanonica and Freiburghaus, 2001;Gerecke et al, 2001;Boreen et al, 2003;Page et al, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Chemical oxidation experiments have shown that the amino acid, tyrosine, is a likely source of 4-hydroxybenzaldehyde and likely also of the acid and ketone forms (Hedges and Parker 1976). Natural DOM sources have been shown to generate 4-hydroxybenzoic acid as well as smaller amounts of the ortho and meta isomers of the molecule during photo-oxidation (Page et al 2011). The fact that 4-hydroxybenzoic acid is predominantly measured in the surface samples suggests that exposure to light may play a role.…”
Section: Differential Metabolite Distributions In the Euphotic Zonementioning
confidence: 99%